Prevalence of Malaria and Associated Knowledge, Attitude, and Practice among Suspected Patients in Bahir Dar Zuria District, Northwest Ethiopia. (19th October 2021) - Dejazmach, Zelalem; Alemu, Getaneh; Yimer, Mulat; Tegegne, Banchamlak; Getaneh, Abel
Abstract : Background . Control and prevention activities have brought substantial decline of malaria incidence in the last two decades in Ethiopia. However, lack of local data on the disease transmission and community knowledge, attitude, and practice about malaria are thought to reverse the trend of malaria in certain areas. Therefore, assessment of the prevalence and community awareness towards malaria plays pivotal role for the success of malaria control and prevention. Objective . To assess malaria prevalence and knowledge, attitude, and practice about malaria among febrile patients in Bahir Dar Zuria district, Northwest Ethiopia. Methods . A facility based crosssectional study was conducted from January to March 2020 among 149 febrile patients attending selected health centers in Bahir Dar Zuria district. Data about knowledge, attitude, and practice about malaria were collected using semistructured questionnaire. Blood sample from each participant was tested for Plasmodium species through malaria rapid diagnostic tests and blood film microscopy. Data were analyzed using statistical software for social sciences version 20. Results . Among 149 participants, 22 (14.8%) were positive for Plasmodium infection at least by one diagnostic methods. Prevalence of P. falciparum and P. vivax was 3.4% and 10.1%, respectively, while that of mixed infection was 1.3%. From the total study participants, 29.5% have good knowledge, 77.2% have positive attitude, and 34.9% have good practice towards malaria. Statistically significant associations were observed on knowledge with age group (X 2 = 10.377, P = 0.035 ), educational level (X 2 = 15.075, P = 0.001 ), family size (X 2 = 7.601, P = 0.022 ), attitude level and practice level. Participants with family size < 5 were 6.841 (95% CI: 2.570-18.206, P ≤ 0.001 ) times more likely to have negative attitude as compared to those with family size ≥ 5 . Conclusions . Prevalence of malaria in the study area was relatively high. Study participants had encouraging attitude; however, their knowledge and practice towards malaria were poor. Therefore, the existing malaria control activities should be supplemented with continuous health educations, aware the community, and ensure participation in the control and prevention activities.